Perfect Meals with Pressure Cooking - Paula G. Harris-Swiatko; Karla P. Shelnutt; Amy Simonne (EDIS)
Preparing great tasting, healthy meals can be a time-consuming task, but pressure cooking is a great way to prepare them in just minutes. Although they may seem old fashioned, pressure cookers are making a comeback, especially with today's busy families who are trying to save both time and money. Pressure cooking is also a healthy cooking option as it maintains the natural flavor and nutrients of food. Delicious, healthy meals are just minutes away with this handy device! This 3-page fact sheet was written by Paula G. Harris-Swiatko, Karla P. Shelnutt, and Amy Simonne, and published by the UF Department of Family, Youth and Community Sciences, March 2012.